Associations between intimate partner violence and women's labor market outcomes in Nigeria - Derek S. Brown; Samantha McNelly; Melissa Meinhart; Ibrahim Sesay; Catherine Poulton; Lindsay Stark (BMC, 2024)
Abstract Background Little is known regarding economic impacts of intimate partner violence (IPV) in humanitarian settings, especially the labor market burden. Examining costs of IPV beyond the health burden may provide new information to help with resource allocation for addressing IPV, including within conflict zones. This paper measures the incidence and prevalence of different types of IPV, the potential relationship between IPV and labor market activity, and estimating the cost of these IPV-associated labor market differentials. Methods The association between labor market outcomes, IPV experience, and conflict exposure among women ages 15-49 in Nigeria were studied using the 2018 Nigeria Demographic and Health Survey and 2013-17 Uppsala Conflict Data Program data. Descriptive analysis was used to identify patterns of IPV and labor outcomes by region. Based on this, multivariable logistic regression models were used to estimate the association between labor market participation and lifetime IPV exposure. These models were combined with earnings data from the United Nations Human Development Report 2021/2022 and a top-down costing approach to quantify the impacts in terms of lost productivity to the Nigerian economy. Results Substantial differences in IPV exposure and labor market outcomes were found between conflict and non-conflict-affected areas. Women with past year or lifetime exposure to physical, emotional, or "any" IPV were more likely to withdraw from the labor market in the past year, although no differences were found for sexual IPV or conflict-affected regions. We estimate an average reduction of 4.14% in the likelihood of working, resulting in nearly $3.0 billion USD of lost productivity, about 1% of Nigeria's total economic output. Conclusions Increased odds of labor market withdraw were associated with several measures of IPV. Withdrawal from the formal labor market sector has a substantial associated economic cost for all of Nigerian society. If stronger prevention measures reduce the incidence of IPV against women in Nigeria, a substantial portion of lost economic costs likely could be reclaimed. These costs underscore the economic case, alongside the moral imperative, for stronger protections against IPV for girls and women in Nigeria.